Efeito da aplicação de filmes de carbono tipo diamante por plasma no destorque de pilares de implantes com conexões cônicas internas - Coelho, Arianne Vallim Pinto [UNESP] (2014)
This study evaluated the effect of the plasma deposition of two diamondlike carbon thin films (DLC) on the reverse torque and adaptation of prosthetic abutments after mechanical cycling. Sixty sets of 11º e 8º tapper connection implants (TCI) and titanium solid abutments were divided in six groups (n=10): GC-8 (control) - 8º TCI with no film deposition; DLC-8 - 8º TCI with DLC deposition; AgDLC-8 - 8º TCI with silver doped DLC (AgDLC); GC-11 (control) - 11º TCI with no film deposition; DLC-11 - 11º TCI with DLC deposition; AgDLC-11 -11º TCI with silver doped DLC (AgDLC); The films were deposited by Plasma Enhanced Chemical Vapor Deposition (PECVD) process. The abutments were tightened with a controlled torque meter device following the manufacturer's recommendations. Mechanical cycling was carried out with a load of 120 Ncm during 2 x 106 cycles with a frequency of 2 Hz (ISO 14801). Afterwards, detorque was measured. Analyses with Scanning Electron Microscopy (SEM) were conducted on three samples of each group before and after mechanical cycling in order to verify the adaptation of the abutments (body and threads). Tribology analyses, as well as Raman Spectroscopy and Energy-Dispersive X-rays Spectroscopy (SDS) analyses were performed for characterization of the different surface treatments. All groups demonstrated reduction of reverse torque values. DLC-8 was the only group that showed an increase on the average reverse torque values